Exploring Diverse Madhhabs' Perspectives on Wearing a Veil among Female Students - Nurdin, Roswati; Dahlan, Mohd Akram bin Dato Dahaman; Rajab; Kamal, Latri; Thalhah (Universitas Islam Negeri Alauddin Makassar, 2024)
The increasing prevalence of veiling among female students is requiring urgent examination. Therefore, this study analyzes veiling during prayer, emphasizing four madhhabs to show varying perspectives and implications for student populations in Ambon State Islamic Institute. A comparative analysis of legal principles is adopted to integrate sociological perspectives using an interdisciplinary approach. Data collection includes interviews, documentation, and bibliographic studies, with emphasis on the influential novel turāś (classic book). The results show that there are three main issues, namely concerns regarding prostration perfection in hadith, debates on mouth and nose closure during prayer, and discussions on intimate body part boundaries for women. In addition, Jumhūr Ulamā (the Majority of Scholars) from al-Shāfi'ī, Hanafī, and Mālikī madhhab concur on visibility necessities in specific situations. Veiling is recommended during prayer unless there is concern for slander. In this context, students' awareness of feminist jurisprudence is stated, advocating for a nuanced understanding beyond a singular perspective. Veiling practices should also be comprehended during prayer among Muslims to urge respect for diverse Islamic opinions. This study reports the urgency of addressing the multifaceted issue and advocates for a comprehensive perspective.